2021
DOI: 10.1007/s42399-021-00912-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Subacute Thyroiditis with COVID-19: a Systematic Review

Abstract: The multisystem effects of SARS-CoV-2 encompass the thyroid gland as well. Emerging evidence suggests that SARS-CoV-2 can act as a trigger for subacute thyroiditis (SAT). We conducted a systematic literature search using PubMed/Medline and Google Scholar to identify cases of subacute thyroiditis associated with COVID-19 and evaluated patient-level demographics, major clinical features, laboratory findings and outcomes. In the 21 cases that we reviewed, the mean age of patients was 40.0 ± 11.3 years with a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 42 publications
4
42
2
3
Order By: Relevance
“…The 17 case reports (16,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38)(39)(40)(41) and the 2 case series (17,35) described carefully the history of patients and their SAT. In this context, it should be highlighted that two recent systematic reviews on a similar topic included 21 (48) and 17 (49) SAT cases, respectively. Our systematic review, conducted 3 months later and conceived with two specific aims, found 27 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The 17 case reports (16,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38)(39)(40)(41) and the 2 case series (17,35) described carefully the history of patients and their SAT. In this context, it should be highlighted that two recent systematic reviews on a similar topic included 21 (48) and 17 (49) SAT cases, respectively. Our systematic review, conducted 3 months later and conceived with two specific aims, found 27 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is usually performed by clinical features, laboratory findings, and ultrasound, whereas fine needle aspiration is reserved for selected cases to differentiate it from a thyroid neoplasm [ 5 ]. SARS-CoV-2 infection can act as a trigger for subacute thyroiditis [ 24 ], and a few cases of subacute thyroiditis were also reported after the SARS-CoV-2 vaccine [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], also referred to as ASIA syndrome [ 16 ]. Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) is responsible for numerous autoimmune disorders such as systemic lupus erythematosus, rheumatoid arthritis, or autoimmune endocrinopathies such as Hashimoto and subacute thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the detection of widespread follicular damage and parenchymal destructions in the thyroid gland in the autopsy series after the SARS pandemic in 2002-2003 strengthens the relationship between SAT and SARS-CoV-2. 28,29 Moreover, many case reports and case series showing the relationship between SARS-CoV-2 and subacute thyroiditis have been published in the literature so far [10][11][12][13][14] . This relationship is so strong that there are cases that develop subacute thyroiditis even after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is so strong that there are cases that develop subacute thyroiditis even after vaccination. 30 The most common symptoms in subacute thyroiditis cases developing after COVID-19 is fever and sore throat (81%) as in other agents 11 Therefore, it is difficult to diagnose SARS-CoV-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation